2017
DOI: 10.1371/journal.pone.0172628
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in cellular pharmacokinetics and pharmacodynamics of elvitegravir in response to ethanol exposure in HIV-1 infected monocytic (U1) cells

Abstract: Ethanol consumption is negatively associated with antiretroviral therapy (ART) adherence and general health in HIV positive individuals. Previously, we demonstrated ethanol-mediated alterations to metabolism of elvitegravir (EVG) in human liver microsomes. In the current study, we investigated ethanol influence on the pharmacokinetic and pharmacodynamic interactions of EVG in HIV infected monocytic (U1) cells. U1 cells were treated with 5 μM EVG, 2 μM Cobicistat (COBI), a booster drug, and 20 mM ethanol for up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Studies with HIV-1-infected macaques have shown increased viral load in the blood and cerebral compartments of chronic-drinking animals [8] . Moreover, previous reports from our lab suggest that ethanol reduced intracellular concentrations of antiretroviral drugs (elvitegravir, darunavir) in the HIV-1-infected U1 cell line [9] , [10] . Ethanol also increased HIV-1 replication despite the presence of elvitegravir [10] .…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…Studies with HIV-1-infected macaques have shown increased viral load in the blood and cerebral compartments of chronic-drinking animals [8] . Moreover, previous reports from our lab suggest that ethanol reduced intracellular concentrations of antiretroviral drugs (elvitegravir, darunavir) in the HIV-1-infected U1 cell line [9] , [10] . Ethanol also increased HIV-1 replication despite the presence of elvitegravir [10] .…”
Section: Introductionmentioning
confidence: 53%
“…Moreover, previous reports from our lab suggest that ethanol reduced intracellular concentrations of antiretroviral drugs (elvitegravir, darunavir) in the HIV-1-infected U1 cell line [9] , [10] . Ethanol also increased HIV-1 replication despite the presence of elvitegravir [10] . Despite this, little is currently known about the cellular pathways involved with alcohol consumption and HIV-1 replication.…”
Section: Introductionmentioning
confidence: 53%
“…Additionally, we recently reported that ethanol exposure decreases the intracellular EVG AUC tot and C max values in the absence of pharmacoenhancer, cobicistat in monocytes (20). Clinically relevant concentration of ethanol (20 mM) exposure to U1 cells resulted in a 11% decrease in AUC tot of DRV compared to DRV alone (t(4) = 4.6, p = 0.0102, student t test, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Further, another commonly used ARV, elvitegravir (EVG), is metabolized by CYP3A4 and a strong CYP3A4 inhibitor such as cobicistat (COBI) is coadministered as a booster to increase EVG bioavailability. Recently, Kumar group showed that the ethanol exposure decreases the intracellular levels of EVG alone and also in combination with COBI in HIV-infected macrophages [19,20]. Subsequently, co-exposing cells to EVG or EVG + COBI along with ethanol showed increased viral replication by 31% and 19%, respectively, relative to control groups that did not receive ethanol [19].…”
Section: Effect Of Alcohol On Cyp3a4-pi and Cyp3a4-integrase Strand Tmentioning
confidence: 99%
“…Recently, Kumar group showed that the ethanol exposure decreases the intracellular levels of EVG alone and also in combination with COBI in HIV-infected macrophages [19,20]. Subsequently, co-exposing cells to EVG or EVG + COBI along with ethanol showed increased viral replication by 31% and 19%, respectively, relative to control groups that did not receive ethanol [19]. Therefore, EVG level should be monitored in HIV patients who consume alcohol to attain sustained virological suppression.…”
Section: Effect Of Alcohol On Cyp3a4-pi and Cyp3a4-integrase Strand Tmentioning
confidence: 99%